Role of Hyaluronic Acid in Dental Implant Surgery - Abdulazeez Muayad Abdulkarem (Academia Open, 2025)
General background: Dental implants are the preferred standard for replacing missing teeth, and successful osseointegration is crucial for their long-term function. Specific background: Hyaluronic acid (HA), a naturally occurring glycosaminoglycan in connective and epithelial tissues, has gained attention for its biological roles in wound healing, regeneration, and antimicrobial activity. Knowledge gap: Despite its known physiological properties, the comprehensive role of HA in enhancing osseointegration and post-surgical healing during dental implantation remains underexplored. Aims: This review investigates the role of HA in dental implant surgery, focusing on its biological mechanisms, physicochemical properties, and clinical applications in promoting bone integration and reducing post-operative complications. Results: Evidence shows that HA facilitates osteoblast adhesion, proliferation, and differentiation, enhances wound healing, and reduces bacterial colonization. When used alone or combined with bone grafts and collagen scaffolds, HA accelerates new bone formation and minimizes inflammation. Novelty: The review highlights HA’s multifaceted bioactivity, including viscoelasticity, bacteriostatic, and antioxidant properties, which collectively improve implant outcomes. Implications: HA demonstrates significant potential as an adjunct biomaterial in dental implantology, enhancing both hard and soft tissue regeneration and improving patient recovery and implant success rates.Highlight : Hyaluronic acid supports bone and soft tissue healing around dental implants by enhancing cell migration and attachment. It helps reduce inflammation, infection risk, and post-surgical discomfort during the implantation process. The unique properties of hyaluronic acid make it beneficial for improving osseointegration and overall implant success. Keywords : Hyaluronic acid, Dental implant, Osseointegration, Wound healing, Bone regeneration